Assessing the impact of the Jal Jeevan Mission (JJM) on human health in the severely arsenic-affected regions of the lower Gangetic plain - Jayanta Das; Arijit Majumder; Sudarshana Sen; Pradip Chouhan; Namita Chakma; Md. Mofizul Hoque; Soumitra Saha (Journal of Health Psychology, 2026)
Access to safe drinking water is vital for human health, as it reduces the risk of waterborne diseases, enhances hydration, and supports overall well-being. This study evaluates health improvements before and after the Jal Jeevan Mission (JJM) across the Community Development (CD) blocks of Murshidabad district. The study identifies significant variation in arsenicosis prevalence, reflecting disparities in exposure and vulnerability. It further assesses perceived health outcomes among implemented and non-implemented JJM households using the Health Belief Model (HBM). The findings show no significant differences in perceived susceptibility and benefits, but notable differences in barriers and health outcomes between JJM-implemented and non-implemented households, indicating potential health improvement with access to safe drinking water. Increased health awareness and adoption of preventive behaviours are associated with perceived health outcomes, as households become increasingly attentive to water-related risks and adaptive practices. This study could benefit stakeholders, regional planners, and policymakers.